Release of outer membrane vesicles in pseudomonas putida as a response to stress caused by cationic surfactants - Heredia, Romina Marisa (2016)
Pseudomonas putida A (ATCC 12633), a degrader of cationic surfactants, releases outer membrane vesicles (OMVs) when grown with tetradecyltrimethylammonium bromide (TTAB) as the sole carbon, nitrogen and energy source. The OMVs exhibit a bilayer structure and were found to be composed of lipopolysaccharides, proteins and phospholipids (PLs) such as cardiolipin, phosphatidylcholine, phosphatidic acid and phosphatidylglycerol (PG). The OMVs showed a marked increase in the PG content, approximately 43 % higher than the amount registered in the parent cells from which the vesicles were derived. After growth of P. putida with TTAB, the amount of lipoprotein covalently cross-linked to the peptidoglycan showed a twofold decrease when compared with values found after growth without the surfactant [16±2 and 28±3 mg (mg cell envelope protein)-1, respectively]. This decrease in the amount of lipoprotein can be related to areas of loss of contact between the outer membrane and the peptidoglycan and, therefore, to OMV production. In addition, due to its amphiphilic nature, TTAB can contribute to OMV biogenesis, through a physical mechanism, by induction of the curvature of the membrane. Taking into account that OVMs were produced when the cells were grown under external stress, caused by the surfactant, and that TTAB was detected in the vesicles [48 nmol TTAB (nmol PL)-1], we concluded that this system of TTAB elimination is a mechanism that P. putida A (ATCC 12633) would utilize for alleviating stress caused by cationic surfactants.